2000
DOI: 10.1302/0301-620x.82b6.0820864
|View full text |Cite
|
Sign up to set email alerts
|

The cost and implications of reoperation after surgery for fracture of the hip

Abstract: R evision operations after fracture of the hip are costly, in both monetary and personal terms. We have assessed whether these costs applied equally to all complications after the primary procedure. We studied 3154 consecutive patients with fracture of the hip and analysed the complications and financial implications related to reoperation within one year of injury. The results showed that revision surgery is not always associated with a significant increase in morbidity, financial cost or mortality, but is di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
20
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 9 publications
3
20
1
Order By: Relevance
“…This is supported by the findings of Holmberg and Thorngren (1988) and Palmer et al (2000) who noted up to a threefold increase in costs, as compared to an uncomplicated case.…”
Section: Discussionsupporting
confidence: 62%
“…This is supported by the findings of Holmberg and Thorngren (1988) and Palmer et al (2000) who noted up to a threefold increase in costs, as compared to an uncomplicated case.…”
Section: Discussionsupporting
confidence: 62%
“…In the long run, the complications associated with internal fixation, will make costs the same for both treatments (Palmer et al 2000, Parker andPryor 2000). In studies reporting on arthroplasties with older cementing techniques and less effective prophylaxis of infections, both the rates of loosening and of sepsis were higher than in contemporary studies.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have shown a 30-40% rate of reoperation after internal fixation and superior function after primary hemi-or total arthroplasty (Johansson et al 2000, Rogmark et al 2002a, b, Roden et al 2003. Cost has been shown to be greater after internal fixation due to the high rate of reoperation, as have morbidity and mortality due to complications (Palmer et al 2000, Rogmark et al 2003. Nevertheless, arthroplasty might be an unnecessary procedure for the 60-70% of the patients who would have an uncomplicated osteosynthesis (Lykke et al 2003).…”
mentioning
confidence: 99%